Time-Varying Beta and Systematic Risk in Nepal’s Banking Sector: an Empirical Analysis - Gyan Mani Adhikari; Prem Lal Adhikari; Santosh Chhetri; Chandan Katuwal (Journal of Balkumari College, 2025)
This study investigates the dynamic nature of systematic risk among eighteen commercial banks listed on the Nepal Stock Exchange (NEPSE) during 2018-2022. Using econometric techniques including GARCH models, Kalman filtering, and rolling window estimation, we analyze daily stock price data to examine time-varying beta coefficients. Results indicate that beta coefficients are not constant but exhibit significant variation in response to market conditions, regulatory changes, and macroeconomic developments. Most banks demonstrate beta values below unity, suggesting defensive characteristics, but substantial heterogeneity exists across institutions. The findings have important implications for portfolio construction, risk management, and regulatory oversight in Nepal’s evolving financial landscape.